PENGARUH SERVICE QUALITY DAN BRAND IMAGE TERHADAP REVISIT INTENTION MELALUI WORD OF MOUTH - Kelvin Candiago; Rudy Pramono (LPSDI Bina Patria, 2024)
A primary clinic is a personal health care facility that provides basic and/or specialist medical services, organized by more than one type of health worker and led by a medical worker. As an industry engaged in the service sector, mGanik Care is asked to maintain the quality of its services in order to maintain a positive image of a clinic. The quality of clinic services is closely related to the image of the clinic. data on the number of patient repeat visits is taken from data on the arrival of old patients. The data shows that in the first 4 (four) months of 2023 the clinic was established, the number was very large. However, over time, the number of patient repeat visits has slowly begun to decline. Some possible causes of the decline in the number of repeat visits of patients at the mGanik Care Diabetes Clinic are promotional media that are too stagnant, not dynamic in keeping up with the times. So that patients are not updated and reduce their interest in visiting again. In addition, promotional media that are not developing create WOM that is not in accordance with expectations. This research is a quantitative study with explanatory analysis. The data collection technique is by questionnaire. The results of this study are all influential on revisit intention other than service quality with an f2 value of 0.011 and t-statistics of 1.148 with a p-value of 0.126. Revisit intention can increase if the branding image carried out by the mGanik Care Clinic is running and right on target so that the mGanik Care Clinic should create a strategy on social and print media to intensify the branding image of the mGanik Care Clinic. So that revisit intention can increase.